2018
DOI: 10.1002/adma.201705189
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks for Separation

Abstract: Separation is an important industrial step with critical roles in the chemical, petrochemical, pharmaceutical, and nuclear industries, as well as in many other fields. Although much progress has been made, the development of better separation technologies, especially through the discovery of high-performance separation materials, continues to attract increasing interest due to concerns over factors such as efficiency, health and environmental impacts, and the cost of existing methods. Metal-organic frameworks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
514
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 923 publications
(545 citation statements)
references
References 235 publications
2
514
0
2
Order By: Relevance
“…[70,[313][314][315][316][317] Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts. [70,[313][314][315][316][317] Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts.…”
Section: Gas Adsorption and Separationmentioning
confidence: 99%
“…[70,[313][314][315][316][317] Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts. [70,[313][314][315][316][317] Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts.…”
Section: Gas Adsorption and Separationmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), also called porous coordination polymers (PCPs), are a class of porous materials commonly obtained by the facile hydrothermal or solvothermal reactions of metal ions and bridging organic ligands at relatively low temperatures . In the past two decades, extensive research has been devoted to developing new MOFs and to exploring their application potential in many fields, such as gas storage, separation, catalysis, sensing, and biomedicine . Early on, a handful of MOFs was found to show a low affinity toward water and a permanent porosity, and this class of hydrophobic MOFs later received increasing attention due to their potential for use in practical adsorption and separation processes, even under humid conditions or in water.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐organic frameworks (MOFs) as new porous materials develop in recent years, which are formed by inorganic metal center and organic ligands . Because of the distinctive architectures, MOFs have broad applications in the fields of catalysis, separation, sensing, drug delivery, as well as gas storage . In recent years, MOFs have also been proved to be precursors for the preparation of porous metal oxides and carbon materials with particular activities .…”
Section: Introductionmentioning
confidence: 99%